Uji In-Vitro Ekstrak Daun Tembakau (Nicotiana tabacum) dan Alamanda (Allamanda cathartica) sebagai Pengendali Hama Helopeltis bradyi pada Bibit Eucalyptus sp. - Andreas Fernandez; Karti Rahayu Kusumaningsih (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2026)
Helopeltis bradyi is an important pest in Eucalyptus sp. seedlings that cause damage and seedling death. Pest control that is usually carried out at HTI (Industrial Forest Plantations) is by using chemical pesticides that have the potential to have a negative impact on the environment. Therefore, an alternative pesticide is needed for the use of botanical pesticides. The purpose of this study is to know the effect of botanical pesticide types and solution formulas on the mortality and severity of H. bradyi pest attack on Eucalyptus sp. seedlings. The research used a Randomized Complete Block Design with two treatment factors, namely the type of botanical pesticide (tobacco and allamanda leaf extract) and the solution formula (10%, 20% and 30%). The observed parameters included pest mortality and severity of H. bradyi pest attack on seedlings with in-vitro test. Results of the research showed that interaction between the type of botanical pesticide in the form of Nicotiana tabacum and Allamanda cathartica leaf extract with 30% solution formula produced a higher mortality of H. bradyi pests with 100% pest mortality. Nicotiana tabacum leaf extract with 30% formula produce 0,00% pest attack severity.